Inter-religious dialogue in Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The article examines the nature and content of inter-religious dialogue, as well as the necessary preconditions for its implementation. In addition, the article reveals peculiarities of the Kazakhstanian model of inter-religious dialogue and substantiates its role and importance in the development of modern society.The authors point out that inter-religious dialogue is one of the major safety strategies, stability and progressive development of society. Since inter-religious dialogue is the basis for inter-religious and inter-ethnic mutual understanding.Key words: dialogue, religion, religious corporation, right, state, confessional relation, ideology, law, constitution.